Case Report: Malignant transformation of ganglioneuroma in the rectovaginal septum to malignant peripheral nerve sheath tumor based on neurofibromas - Xi, Xiaoxiao; Cheng, Hui; Huang, Shanyu; Wang, Chen; Ye, Mingzhu; Sun, Xin (Frontiers in Oncology, 2025)
Malignant peripheral nerve sheath tumor (MPNST) is a type of soft tissue sarcoma that commonly occurs in the trunk, limbs, and head and neck regions, but rarely in the pelvic area. Nearly half of MPNST cases are secondary to neurofibromatosis type 1 (NF1). This case report discusses a 29-year-old woman diagnosed with NF1 and pseudohermaphroditism, who presented with a large mass in the rectovaginal septum. Several years prior, a biopsy had identified the mass as a ganglioneuroma (GN). The mass was surgically removed via a vaginal approach, and postoperative pathology confirmed MPNST arising from NF1. In addition, this report provides a brief review of the relevant literature.